PENGARUH LITERASI HALAL DAN RELIGIUSITAS TERHADAP MINAT PEMBELIAN PRODUK BERLABEL HALAL STUDI PADA MAHASISWA UIN RADEN INTAN LAMPUNG - Rahmat; Chandra Okspendri; Vicky F Sanjaya (Program Studi Ekonomi Syariah, 2022)
At this time the demand for halal products among the public continues to increase, therefore there is a need to increase halal literacy in society, not only apart from the halal logo, but also how literacy relates to the process of the product consumed from the start to finish. Halal literacy among students, especially at UIN Raden Intan Lampung students, is currently only limited to how to put a halal logo on a product, therefore there is a need for concrete steps from both stakeholders and the students themselves in increasing Halal Literacy. This study used a quantitative method, with a population of UIN Raden Intan Lampung students. The data collection technique used was a questionnaire on 113 students with a total of 14 questions. From the results of this study, it was found that Halal Literacy and Religiosity had a positive and significant effect on the intention to buy products labeled halal in UIN Raden Intan Lampung students.